The Effect Of Company Growth, Environmental Performance, And Profitability On Company Value In Mining Industry Companies Listed On The Indonesian Stock Exchange For The Period 2020-2022 - Fachrezi, Athallah; Affandy, Didied Poernawan (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
Company value is an important indicator for company owners and investors, as a high company value will increase shareholder wealth. This study aims to examine the influence of company growth, environmental performance, and profitability on company value among mining companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022. The research employed a quantitative method using secondary data from 17 mining companies listed on the IDX, yielding 51 observations. The results show that company growth and environmental performance do not significantly influence company value, whereas profitability has a significant positive effect. This indicates that higher profitability is associated with higher company value.